Reference Model for Effective Performance and Availability Monitoring in Large Scale Software Systems - Ramakrishnan, Raghu; Kaur, Arvinder (International Journal of Computer Sciences and Engineering, 2019)
The monitoring of different parts of the software stack is essential for ensuring acceptable performance and availability of large scale heterogeneous software systems. However, given that a large amount of data is generated by various parts of the software stack, identifying the minimum set of data elements for inclusion under the initial monitoring umbrella is challenging. Although the elements are similar across the majority of the projects, we have seen that teams often spend considerable effort and time in identifying them. In this paper, we present a layered monitoring reference model, with different layers targeting different parts of the software stack using appropriate data elements. The model provides guidance on the minimum set of data elements, drawing on learnings from more than 20 real-life projects. The model also explains the data elements and the motivation for including them in the model.